Antibodies against the SARS-CoV-2 S1-RBD cross-react with dengue virus and hinder dengue pathogenesis - Cheng, Yi-Ling; Chao, Chiao-Hsuan; Lai, Yen-Chung; Hsieh, Kun-Han; Wang, Jen-Ren; Wan, Shu-Wen; Huang, Hong-Jyun; Chuang, Yung-Chun; Chuang, Woei-Jer; Yeh, Trai-Ming (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread globally since December 2019. Several studies reported that SARS-CoV-2 infections may produce false-positive reactions in dengue virus (DENV) serology tests and vice versa. However, it remains unclear whether SARS-CoV-2 and DENV cross-reactive antibodies provide cross-protection against each disease or promote disease severity. In this study, we confirmed that antibodies against the SARS-CoV-2 spike protein and its receptor-binding domain (S1-RBD) were significantly increased in dengue patients compared to normal controls. In addition, anti-S1-RBD IgG purified from S1-RBD hyperimmune rabbit sera could cross-react with both DENV envelope protein (E) and nonstructural protein 1 (NS1). The potential epitopes of DENV E and NS1 recognized by these antibodies were identified by a phage-displayed random peptide library. In addition, DENV infection and DENV NS1-induced endothelial hyperpermeability in vitro were inhibited in the presence of anti-S1-RBD IgG. Passive transfer anti-S1-RBD IgG into mice also reduced prolonged bleeding time and decreased NS1 seral level in DENV-infected mice. Lastly, COVID-19 patients’ sera showed neutralizing ability against dengue infection in vitro. Thus, our results suggest that the antigenic cross-reactivity between the SARS-CoV-2 S1-RBD and DENV can induce the production of anti-SARS-CoV-2 S1-RBD antibodies that cross-react with DENV which may hinder dengue pathogenesis.